Dividend Policy and Firm Value: The Mediating Role of Financial Performance - Nisa, Zaharatun; Haiqal, Muhammad; Yusnidar, Cut; Saputra, Ryanda; Yanti, Evi Maulida (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
In the business world and capital markets, firm value is an important indicator that reflects the company's performance, prospects, and attractiveness in the eyes of investors. One factor that is believed to influence firm value is dividend policy, which is the management's decision to distribute profits to shareholders or retain them for the company's investment needs. In the world of investment and capital markets, dividend policy is one of the important factors that can influence investor perceptions of a company's value. This policy reflects. The method used in this study is secondary data through the financial statements of manufacturing companies that meet the sample criteria of 12 companies in a 5-year observation period. Data processing in the study using the eviews application with the selection of CEM, FEM, and REM models was carried out to determine the method that is appropriate for the research conducted, then the chow test, hausman test, and lagrange multipler test were used. From the results of data processing and analysis of the problems carried out, it can be concluded that the financial performance variable is unable to mediate the effect of dividend policy on firm value, this is because dividend policy acts as an external factor that directly influences firm value, without the need to go through a mechanism to improve financial performance. Dividend policy has a positive and significant effect on firm value. This shows that companies that consistently distribute dividends provide a positive signal to investors regarding financial stability and future profit prospects, while financial performance does not affect the value of the company. The implication of this finding suggests that in the context of the consumer goods industry, investor perceptions of firm value are more influenced by external signals such as dividend distribution, rather than by internal indicators such as ROA.